Anaisa Perencanaan Desain Jaringan Broadband Fiber To The Home (FTTH) Di Universitas Riau - Dwi Putra Retdha Yuhana; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This script discusses about FTTH network design planning analyzes each respective faculty buildings which exist at the University of Riau. Fiber To The Home (FTTH) using a broadband Internet connection that uses fiber-optic cables, optical-based systems can deliver a wide array of digital information, such as voice, video, data, known as the triple play. Riau University located in panam has 7 faculty reached its 700 acres. The results of the design of the Broadband network Fiber To The Home of the University of Riau need Optical Network Terminal as much as 209 fruit, the Optical Distribution Point used totaled 34 fruit and Optical Distribution Cabinet 1 alone is enough backup area University of Riau with all types of ODC 144 24 core capacity.Keywords : FTTH, University of Riau